Influence of rainfall events on zooplankton community characteristics and feeding habits in estuarine–coastal environments - Jeong, Young Seok; Choo, Seohwi; Soh, Ho Young (Frontiers in Marine Science, 2022)
In temperate estuaries, rainfall causes environmental fluctuations, such as salinity and suspended particulate matter (SPM), and can affect zooplankton distribution patterns. This study focused on the effect of temporary freshwater inflow on the composition of major zooplankton species and changes in their ecological status in the Seomjin River estuary before (June) and after (August) rainfall in 2018. Environmental data were collected from 14 and 15 stations before and after rainfall, respectively. All factors except for chlorophyll-a (Chl-a) concentration differed significantly before and after rainfall (p<0.05), and a salinity gradient extended to Yeosu Bay from Gwangyang Bay. Zooplankton abundance decreased significantly after rainfall. There was a high correlation between indicator species abundance and environmental factors after rainfall (correlation coefficient: 0.7521); however, the indicator species and environmental factors did not exhibit a significant correlation with salinity before rainfall. In terms of feeding habit composition, the carnivore proportion showed a significant decrease after rainfall compared to before rainfall (p<0.001), while the particle feeder proportion showed a significant increase after rainfall compared to before (p<0.001). In particular, Corycaeus spp. contributed significantly to the decrease in carnivore abundance after rainfall. Among the particle feeders, Copepodites significantly increased in abundance after rainfall. Carnivore abundance was negatively correlated with salinity, and particle feeder abundance was positively correlated with potential prey sources (SPM and Chl-a concentration), suggesting that particle feeders respond to the food-rich environment after rainfall.